2021
DOI: 10.1139/cjpp-2020-0276
|View full text |Cite
|
Sign up to set email alerts
|

The role of aldosterone inhibitors in cardiac ischemia–reperfusion injury

Abstract: Myocardial ischaemia-reperfusion (I/R) injury is well known term for paradoxal exacerbation of cellular destruction and dysfunction, after the restoration of blood flow to previously ischaemic heart. A vast number of studies that has demonstrated the role of mineralocorticoids in cardiovascular diseases is based on the use of pharmacological mineralocorticoid receptor antagonists (MRA) such as spironolactone and eplerenone. This review paper aimed to summarize current knowledge on the effects of MR antagonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Both leupeptin and compound MDL28170 (inhibitors of matrix metalloproteinases) were observed to prevent I/R injury by depressing the activation of proteolytic enzymes in the heart [ 26 , 102 , 103 ]. Furthermore, various aldosterone receptor antagonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors have been observed to attenuate I/R injury as well as infarct size due to myocardial infarction by multiple mechanisms including inflammation and oxidative stress [ 104 , 105 ]. Because of the multifactorial basis of I/R injury, a wide variety of drugs such as cyclosporin, colchicine, tocilizumab, glucagon-like peptide 1 antagonist and modulators of different protein kinases (acting at different target sites) have been demonstrated to limit myocardial infarct size as well as prevent cardiac arrhythmias, cellular necrosis, apoptosis, and metabolic defects [ 99 , 106 , 107 , 108 ].…”
Section: Pharmacotherapy Of I/r Injury To the Heartmentioning
confidence: 99%
“…Both leupeptin and compound MDL28170 (inhibitors of matrix metalloproteinases) were observed to prevent I/R injury by depressing the activation of proteolytic enzymes in the heart [ 26 , 102 , 103 ]. Furthermore, various aldosterone receptor antagonists and sodium-glucose cotransporter 2 (SGLT2) inhibitors have been observed to attenuate I/R injury as well as infarct size due to myocardial infarction by multiple mechanisms including inflammation and oxidative stress [ 104 , 105 ]. Because of the multifactorial basis of I/R injury, a wide variety of drugs such as cyclosporin, colchicine, tocilizumab, glucagon-like peptide 1 antagonist and modulators of different protein kinases (acting at different target sites) have been demonstrated to limit myocardial infarct size as well as prevent cardiac arrhythmias, cellular necrosis, apoptosis, and metabolic defects [ 99 , 106 , 107 , 108 ].…”
Section: Pharmacotherapy Of I/r Injury To the Heartmentioning
confidence: 99%
“…This leads to inflammation, oxidative stress, and apoptosis in the cardiac tissues [ 104 ]. MR antagonists have proven effective in limiting the ischemia/reperfusion-induced tissue damage and, correspondingly, the infarction zone [ 105 ]. Fraccarollo et al showed that a cardiomyocytespecific deletion of the MR in mice could reduce post-myocardial infarction (post-MI) cardiac remodeling [ 106 ].…”
Section: Over-active Mr In the Absence Of Elevated Aldosterone Levelsmentioning
confidence: 99%
“…Although the restoration of blood (reperfusion) to an ischemic heart is essential in order to save the myocardium, it can paradoxically cause irreversible myocardial damage termed “ischemia–reperfusion (I–R) injury”. Reperfusion after an ischemic episode may result in cardiomyocyte dysfunction caused by the production of reactive oxygen species (ROS), intracellular and mitochondrial Ca 2+ overload, and the accumulation of inflammatory cells [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%